2009
DOI: 10.1002/pssb.200945455
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer study of nanosized Co-Ni ferrite Co x Ni1−x Fe2 O4 (0 ≤ x  ≤ 1) particles

Abstract: Nanocrystalline Co-Ni ferrite Co x Ni 1Àx Fe 2 O 4 (0 x 1) have been synthesized by using the PVA sol-gel method. All the samples were examined by powder X-ray diffraction (XRD) measurements and found to be single phase spinel. The Mössbauer spectra at room temperature were recorded by using a Mössbauer spectrometer and were fitted by two magnetic sextets A and B. An electron configuration of 3d 5 4s k instead of 3d 5 for Fe 3þ in tetrahedral (A) sites is taken to explain qualitatively the variation of such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The areas of the two sub-spectra were found to be in ratio A : B = 78 : 22. Hyperfine parameters are typical for those reported in cobalt ferrites, [54] see Table S2 in Supporting Information.…”
Section: Products Of the Thermal Decompositionmentioning
confidence: 58%
“…The areas of the two sub-spectra were found to be in ratio A : B = 78 : 22. Hyperfine parameters are typical for those reported in cobalt ferrites, [54] see Table S2 in Supporting Information.…”
Section: Products Of the Thermal Decompositionmentioning
confidence: 58%
“…In a Mössbauer study of nanosized Co-Ni ferrites synthesized by the PVA sol-gel method [65], the authors fit the spectra with only two subspectra, one for tetrahedral and one for octahedral sites; but in our case a more accurate fit was done with one subspectra for tetrahedral and two for octahedral sites, in accordance to other authors who found more than one octahedral site for different cation substituted ferrites [66,67]. The use of an external magnetic field and low temperature spectra are sometimes necessary to perform a proper distinction between the contributions from tetrahedral and octahedral sites, due to a strong overlapping of lines in both cases.…”
Section: Resultsmentioning
confidence: 99%
“…Sample preparation of Co x Ni 1 À x Fe 2 O 4 (x¼ 0.1, 0.3, 0.5) nanoparticles was carried out by using the PVA Sol-Gel method as described in our previous report [15]. Stoichiometric amounts of cobalt nitrate, nickel nitrate and ferric nitrate were dissolved in distilled water and the solution was added to the aqueous PVA solution afterwards with continuous stirring for 30 min.…”
Section: Methodsmentioning
confidence: 99%